Monosyllabic and polysyllabic words used in Togay Murod's "The Night of the Neighing Horse" - Norova Shahodat Bakhodirovna; Nabizada Zainullah (Genius Journals, 2025)
This article describes the use of single-meaning and multi-meaning words in the language of Togay Murod's story, and the writer's skill in using these tools to reveal the essence of the work.
Keywords: literary text; term; proverb